The Development Of Medicine In Western Europe During The Renaissance (Zien Journal of Social Sciences and Humanities, 2025)
The Renaissance, also known as the "Rebirth", was a significant societal shift in Europe spanning from the 14th to the 17th century. Therefore, the beginnings of the Renaissance were not at all intentional but rather the outcome of various unconnected events and occurrences. The dissection of human cadavers was forbidden by both the Catholic Church and the Coran, which resulted in a slow advancement in the understanding of anatomy. During this period, influential medical figures and scholar humanists achieved significant progress in the fields of medicine and surgery. First to be examined will be Linacre, Erasmus, Leoni cello, and Sylvius, as they all belong to the early classic Renaissance period. Andreas Vesalius and Ambroise Paré then made significant contributions to anatomy and surgery, respectively, through the publication of their works "Human Factory" (1543) and "The Apologie and Treatise of Ambroise Paré." During the transition from the Renaissance to the New Science era, William Harvey, a renowned British doctor and researcher in the field of cardiovascular health, uncovered the concept of general circulation. In 1628, he released his discoveries in the book "The Motu Cordis."